Strengthening Cultural Literacy and Citizenship through ENSHI Training for High School/Vocational School students in Tasikmalaya Regency - Tanshzil, Sri Wahyuni; Hadian, Vini Agustiani (Jurnal Civicus, 2024)
Cultural literacy and citizenship are important skills that must be mastered by students in facing global cultural flows (globalization) which have the potential to eliminate local cultures and weaken national identity. However, at a contextual level, the existence of local culture is increasingly worrying and the normative values of Indonesian society are increasingly biased because they are starting to be influenced by foreign culture, adding to the rapid fading of national identity and loss of personal potential. This is the background for researchers to conduct E-ENSHI training for high school/vocational school students in Tasikmalaya Regency to strengthen cultural and civic literacy. This research uses a quantitative approach with descriptive methods, data collection is carried out using questionnaires and literature studies. Based on the research results, it can be seen that there is a positive impact from the use of E-ENSHI in strengthening the cultural literacy and citizenship of high school/vocational school students in Tasikmalaya district.